Effect of Cu2+ substitution on structural, magnetic and transport properties of Fe2.5Zn0.5−xCuxO4 - Rahman, M. Arifur; Rahman, M. Azizar; Hossain, A.K.M. Akther (Journal of magnetism and magnetic materials, 2014)
Polycrystalline Fe2.5Zn0.5−xCuxO4 ferrites (where y varies from 0 to 0.45 in steps of 0.05) were prepared by the standard solid state reaction technique. The X-ray diffraction patterns consist of major cubic spinel Fe2.5Zn0.5−xCuxO4 phase with minor impurity phases (Fe2O3 and CuO). The lattice constant decreases slightly with increasing Cu content. The bulk density and average grain size increases with Cu content up to x=0.30 due to the lattice diffusion. The initial permeability and relative quality factor increases with increasing Cu content up to x=0.30. It is attributed to the migration of Fe3+ in the octahedral sublattice and a decrease beyond this content is due to the spin canting effect. The dielectric constant and loss tangent decrease with increasing frequency of the applied alternating electric field because of dielectric polarization, which is similar to the conduction phenomenon. The ac conductivity increases with increasing frequency for the samples x≤0.15 due to the small polaron hopping conduction. The frequency-independent conductivity is found below a certain frequency for the samples x≥0.20 and dominated over a wide frequency range (up to 0.5MHz) for the sample containing x=0.30 due to band conduction. •The Fe2.5Zn0.2Cu0.3O4 shows optimum value of ρB,ξ,μi,σac,ε and RQF.•Frequency-independent σac is found up to 0.5MHz for Fe2.5Zn0.2Cu0.3O4.•The hopping frequency increases with Cu content up to x=0.3.•Hopping conduction is observed for the samples x≤0.15.•Both band and hopping conductions are observed for the samples x≥0.20.